Avaliação da usinabilidade de cilindros para laminação de tiras a quente - Pernambuco, Luiz Rodrigo Alegre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The use of tests to evaluate the machinability of the material may be a determining factor in the viability of manufacturing processes, and contribute to planning the cost, time and in the search for the quality of the product through development of strategies and machining technologies. When the machined product is rolling mill roll, who played as a tool in the milling process the need for such development becomes clear when is examined the requirements for high performance rolling mill roll and identifies that they are the same requirements for high performance machining tools: wear resistance, toughness and hardness. So, this work proposes a machinability test in laboratory seeking the evaluation of two materials for rolling mill rolls: an indefinite chilled double poured cast iron and a microalloyed indefinite chilled double poured cast iron. The test was performed by milling with three edges of carbide on a machining center and the machinability analysis of this work was done by the criterion of end of life of the machining tool. The work found that the addition of alloying elements on the chemical composition of the rolling mill rolls directly influenced the machinability of microalloyed indefinite chilled double poured cast iron, because the volume fraction of carbides VC increased by almost three times in this material resulting in an abrasive wear on the edges of cutting tools

A utilização de ensaios de avaliação da usinabilidade dos materiais pode ser um fator determinante na viabilidade de processos de fabricação, contribuindo no planejamento dos custos, prazos e na busca pela qualidade do produto através de desenvolvimentos de estratégias e tecnologias de usinagem. Quando o produto usinado é um cilindro, que faz o papel de ferramenta no processo de laminação, a necessidade de tal desenvolvimento fica clara quando se analisa os requisitos para alta performance de cilindros de laminação e se identifica que eles são os mesmos requisitos para alta performance de insertos de usinagem: resistência ao desgaste, tenacidade e dureza. Assim esse trabalho propõe um ensaio de usinabilidade em laboratório para a avaliação de dois materiais de cilindros de laminação: o ferro fundido indefinido e o ferro fundido indefinido microligado. O ensaio foi executado através do fresamento com três arestas de metal duro em um centro de usinagem e a análise de usinabilidade foi feita pelo critério de fim de vida da ferramenta de usinagem. Foi constatado que a adição de elementos de liga na composição química dos cilindros influenciou diretamente na usinabilidade do ferro fundido indefinido microligado, pois a fração volumétrica de carbonetos VC aumentou em quase três vezes nesse material resultando em um desgaste abrasivo nas arestas das ferramentas de corte
Evaluation of machinability of rolling mill rolls for hot strips mill
Keywords: Metais - Usinabilidade; Laminação (Metalurgia); Ferro fundido; Desgaste mecânico; Ferramentas para cortar metais; Usinagem; Metals Machinability